2019
DOI: 10.1088/1674-1056/28/6/068701
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of overstretching DNA–RNA hybrid duplex*

Abstract: DNA–RNA hybrid (DRH) plays important roles in many biological processes. Here, we use a thermodynamic theory to analyze the free energy and unpeeling properties of the overstretching transition for the DRH molecule and compare the results with double-helix DNA. We report that the RNA strand of DRH is easier to get unpeeled than the DNA strand while the difficulty in unpeeling the double helix DNA lies in between. We also investigate the sequence effect, such as GC content and purine content, on the properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When temperature is above 16 C, or the NaCl concentration is low, DRH undergoes a hysteretic transition, indicating the presence of unpeeling process, which results in a stretched ssDNA and probably a coiled ssRNA (note that because of the configuration used in their experiments, only the RNA strand can be unpeeled there without breaking the tether), and such peeled single strands are difficult to anneal back to reform the hybrid duplex. Our previous theoretical study indicated that during overstretching, peeling from RNA strand is more favored than peeling from DNA (55). A recent experimental study performed by Melkonyan et al (56) also supports this point.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…When temperature is above 16 C, or the NaCl concentration is low, DRH undergoes a hysteretic transition, indicating the presence of unpeeling process, which results in a stretched ssDNA and probably a coiled ssRNA (note that because of the configuration used in their experiments, only the RNA strand can be unpeeled there without breaking the tether), and such peeled single strands are difficult to anneal back to reform the hybrid duplex. Our previous theoretical study indicated that during overstretching, peeling from RNA strand is more favored than peeling from DNA (55). A recent experimental study performed by Melkonyan et al (56) also supports this point.…”
Section: Introductionmentioning
confidence: 65%
“…Therefore, three components, namely ssDNA, ssRNA, and S-form DRH (S-DRH), could remain after overstretching. Notice, here, we do not consider small DRH ''bubble'' formation because the theoretical calculation has shown that the ''bubble'' formation is energetically less favorable in comparison with unpeeling and formation of S-DRH, even for AT/UA-rich sequences (55). Then, for traces whose FECs do not show obvious hysteresis in the force range of 75-80 pN, we have developed a method (see Supporting Materials and Methods for details) to analyze the fraction of each components left at the end of stretching (i.e., F ¼ 80 pN).…”
Section: Heterogeneity Of Drh Overstretching Transitionsmentioning
confidence: 99%